Pengaruh Produksi Karet, Nilai Tukar, dan Inflasi Terhadap Volume Ekspor Karet Indonesia Tahun 2019 s.d. 2023 - Izzah, Nidaul; Putra Bujana, Cesar Ardilla (Institut Ilmu Sosial dan Manajemen STIAMI, 2024)
This study aims to analyze the influence of rubber production, the rupiah exchange rate against the US dollar, and inflation on Indonesia's rubber export volume from 2019 to 2023, both partially and simultaneously. Using an explanatory research method with a quantitative approach, secondary data from the Central Statistics Agency was processed using multiple linear regression analysis through IBM SPSS 29. The findings reveal that simultaneously, the variables of rubber production, exchange rate, and inflation do not significantly affect export volume. Partially, rubber production has a positive and significant effect on export volume, with a (t)-value higher than the critical (t)-table value. Conversely, the exchange rate shows no significant effect ((t)-value < (t)-table). Inflation demonstrates a significant but negative influence, with a (t)-value lower than (t)-table and a significance level of 0.047 (